Solid recovered fuel production through the mechanical-biological treatment of wastes - Velis, C. A. (Cranfield University, 2010)
This thesis is concerned with the production of solid recovered fuel (SRF) from municipal solid waste using mechanical biological treatment (MBT) plants. It describes the first in-depth analysis of a UK MBT plant and addresses the fundamental research question: are MBT plants and their unit operations optimised to produce high quality SRF in the UK? A critical review of the process science and engineering of MBT provides timely insights into the quality management and standardisation of SRF use in Europe. Quantitative fuel property data for European SRFs are collated and analysed statistically in a detailed examination of the fuel quality achievable from MBT-derived SRF. The experimental research herein applies statistical sampling, analytical characterisation and materials flow analysis to a new generation, fully operational SRF-producing MBT plant. To the author’s knowledge, this is the first detailed analysis of this kind for a UK plant. Individual process flows from mechanically processed waste are characterised using a series of fuel properties in line with the European product standards for SRF, and confidence limits in these properties quantified. New data on SRF quality, including biogenic content, is provided. In seeking understand the variability in waste heterogeneity and its impact on SRF production in an MBT plant, material flow analysis is applied across the MBT flowsheet to compute transfer coefficients for individual unit operations. This provides a basis for critically evaluating the performance of this specific MBT and the extent to which is it optimised for SRF production. Cont/d.